PENGARUH MEDIA KIPAS (KINCIR ANGIN PANEL SURYA) TERHADAP AKTIVITAS PEMBELAJARAN IPA SISWA KELAS IV DI SANGGAR BIMBINGAN KAMPUNG BARU MALAYSIA - Sihotang, Tio Hanif; Sari, Mawar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of using windmill-based learning media (solar panel windmill) in improving students' understanding and engagement in science learning. The research was conducted at Sanggar Bimbingan Kampung Baru, Malaysia, with fourth-grade students as participants. A pre-test and post-test design were implemented to measure learning outcomes before and after using the media. Data were analyzed using descriptive and inferential statistical methods, including validity, reliability, normality, and paired sample t-tests. The results indicate a significant improvement in students' learning outcomes, with post-test scores showing higher comprehension levels compared to the pre-test. The validity and reliability tests confirm that the research instrument is trustworthy, while the normality test ensures that the data are normally distributed. The paired sample t-test further supports that the use of the solar panel windmill has a significant positive impact on students' science learning. Thus, this learning media is proven to be an effective tool in enhancing students' academic performance and engagement in science education.